DEVELOPING KAHOOT! AS STUDENTS’ WORKSHEET IN TEACHING READING COMPREHENSION OF RECOUNT TEXT AT GRADE VIII OF SMP KEMALA BHAYANGKARI MEDAN - Irmaya Br. Sitepu; Nora Ronita Dewi (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
The objective of this study was to develop an appropriate student’s worksheet forgrade eight students in order to assess students’ reading comprehension of recountmaterial using Kahoot! which is a game-based application. This study was carriedout at SMP Kemala Bhayangkari Medan. This study would be undertaken throughthe use of Research and Development (R & D) methods. The research would bebased on Borg and Gall's technique of Research and Development whichcontained six stages; gathering information and data, analysing data, designingmaterial, validating by the experts, revising material, and the last was finalproduct. The data was gathered through the distribution of questionnaire andinterviewed 27 students and an English teacher to see the students’ need. Thestudy's conclusion resulted in the development of the Kahoot! platform, whichmay be used as a worksheet for students to practice reading comprehension of therecount text. There were three aspects that are assessed for the feasibility test ofstudent worksheets by experts; presentation aspects, language aspects, and layoutaspect. In percentage terms, the average score of expert validations was 92.8%,the presentation aspect was 92%, the language aspect was 97%, and the layoutwas 100%. The average worksheet score was 95.4% which was categorized asvery good and it was suggested to use in English class especially for readingrecount text of grade eight.